1968
DOI: 10.1139/z68-055
|View full text |Cite
|
Sign up to set email alerts
|

Gastropods as intermediate hosts of Pneumostrongylus tenuis Dougherty of white-tailed deer

Abstract: From May to October, 1966, gastropods from three different habitats on Navy Island, Ontario, were examined for larvae of Pneumostrongylus tenuis. Of 9940 examined individually, 4.2% contained larvae. A mean of 2.9 larvae was recovered from each infected gastropod. Deroceras laeve and Zonitoides nitidas were the most abundant and commonly infected species. The incidence of infective larvae in adult D. laeve from a wet forested area rose to 25% by late June but dropped to 1.5% during July, coinciding with the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 4 publications
2
55
0
Order By: Relevance
“…Gastropods become relatively inactive when moisture is low (Burch, 1956), and deer feces and surface soil (both with first-stage larvae of P. tenuis) become dry. The likely result is increased mortality of P. tenuis larvae and curtailed transmission (see Lankester and Anderson, 1968). Beetle (1989) indicated that extremes of temperature, short periods between killing frosts and little moisture likely contribute to fewer gastropods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastropods become relatively inactive when moisture is low (Burch, 1956), and deer feces and surface soil (both with first-stage larvae of P. tenuis) become dry. The likely result is increased mortality of P. tenuis larvae and curtailed transmission (see Lankester and Anderson, 1968). Beetle (1989) indicated that extremes of temperature, short periods between killing frosts and little moisture likely contribute to fewer gastropods.…”
Section: Discussionmentioning
confidence: 99%
“…Parelaphostrongylus tenuis, called meningeal worm, is a common parasitic nematode of white-tailed deer (WTD; Odocoileus virginianus), throughout the deciduous mixed-hardwood forests of eastern North America (Lankester, 2001). It has been reported as far west as western Manitoba (Bindernagel and Anderson, 1972) in Canada and western Nebraska in the United States (Oates et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal temperature and precipitation influence the range and prevalence of meningeal worm infection via gastropod distribution and larval survival (Lankester and Anderson 1968;Shostak and Samuel 1984;Forrester and Lankester 1998;Wasel et al 2003). We obtained data on precipitation and temperature from 160 weather stations in North Dakota for the period 1963-2005 (National Oceanic and Atmospheric Administration 2015).…”
Section: Climate Modelsmentioning
confidence: 99%
“…The meningeal worm has an indirect life cycle requiring one of several species of terrestrial gastropods as intermediate hosts (Lankester and Anderson 1968). It can cause fatal neurologic disease in several species of accidental hosts, including moose (Alces alces), elk (Cervus canadensis), and mule deer (Odocoileus hemionus; Lankester 2001), although its life cycle is generally only completed in white-tailed deer (Anderson and Prestwood 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation